The Effect of the Exploration and Exploitation of Oil and Gas on Indonesian Economic Growth - Yassir Achmad; Sofyan Syahnur; Chenny Seftarita (Research Collaboration Community (RCC), 2022)
The era of globalization and accelerated economic growth, as well as various kinds of industrial and technological transformations, are currently causing or triggering very concrete environmental problems, one of which is in terms of the growth in consumption of non-renewable energy, namely oil and natural gas. Oil and gas reserves are part of the socio-economic problems in Indonesia. It is known that oil and gas reserves are spread throughout almost all aspects of Indonesia. However, the utilization of the potential reserves of oil and natural gas resources in Indonesia is still not fully optimized. So that the potential for oil and gas reserves in Indonesia still does not fully have a more significant impact on Indonesia's economic growth. This study examines the influence of oil and gas exploration and exploitation in Indonesia on economic growth in Indonesia. This study used data on Indonesia's GDP and Exploitation and Exploitation of Indonesian Oil and Gas in a time series (1996-2021). In analyzing the data, this study used multiple linear regression. The results showed that the exploration and exploitation of oil and gas have a positive and significant effect on economic growth in Indonesia. It is hoped that this study can serve as an impetus for the government in making regulations and regulations directly related to exploration and exploitation activities both upstream and downstream of oil and gas and as encouragement and motivation for governments directly involved with upstream and downstream oil and gas activities. In addition, to issue policies in the form of continuing to prioritize technological development innovations, especially in the oil and gas sector. It is also hoped that the production results obtained from oil and natural gas exploration and exploitation activities can be more optimal and impact national energy security, state revenues, and Indonesia's economic growth.